Steamships and their story - Chatterton, E. Keble (Edward Keble), 1878-1944 (Salt Lake City, UT : Project Gutenberg, 2023)
"Steamships and their story" by E. Keble Chatterton is a historical account written in the early 20th century. The book chronicles the evolution and significance of steamships, tracing their development from early mechanical constructions to their status as integral vessels in modern transportation. Chatterton aims to reveal the rich history and influence of steamships on global trade and society, capturing their unique blend of technological innovation and romance. At the start of the narrative, the author introduces the premise of the book, explaining that it follows his earlier work on sailing ships. Chatterton asserts that the advancement of steamships parallels societal progress, having significantly transformed mobility and commerce in a relatively short period. He reflects on the challenges and triumphs of inventors and engineers in pushing the boundaries of maritime technology, emphasizing the steamship's role in overcoming the limitations of wind-dependent sailing vessels. The opening establishes a context of fascination and respect for the steamship as not just a mode of transport but as a pivotal element shaping modern civilization. (This is an automatically generated summary.)
Release date is 2023-11-05
Peter Becker, Charlie Howard, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Shipbuilding; Steamboats